Enhanced enzymatic activity exerted by a packed assembly of a single type of enzyme. Issue 34 (4th August 2020) - Dinh, Huyen; Nakata, Eiji; Mutsuda-Zapater, Kaori; Saimura, Masayuki; Kinoshita, Masahiro; Morii, Takashi
Abstract : The enzymatic reactions proceeded faster in the packed than in the dispersed state. Abstract : In contrast to the dilute conditions employed for in vitro biochemical studies, enzymes are spatially organized at high density in cellular micro-compartments. In spite of being crucial for cellular functions, enzymatic reactions in such highly packed states have not been fully addressed. Here, we applied a protein adaptor to assemble a single type of monomeric enzyme on a DNA scaffold in the packed or dispersed states for carbonic anhydrase. The enzymatic reactions proceeded faster in the packed than in the dispersed state. Acceleration of the reaction in the packed assembly was more prominent for substrates with higher hydrophobicity. In addition, carbonic anhydrase is more tolerant of inhibitors in the packed assembly. Such an acceleration of the reaction in the packed state over the dispersed state was also observed for xylose reductase. We propose that the entropic force of water increases local substrate or cofactor concentration within the domain confined between enzyme surfaces, thus accelerating the reaction. Our system provides a reasonable model of enzymes in a packed state; this would help in engineering artificial metabolic systems.